Braking of road vehicles - Day, Andrew J. (Butterworth-Heinemann, 2014)
Starting from the fundamentals of brakes and braking, Braking of Road Vehicles covers car and commercial vehicle applications and developments from both a theoretical and practical standpoint. Drawing on insights from leading experts from across the automotive industry, experienced industry course leader Andrew Day has developed a new handbook for automotive engineers needing an introduction to or refresh on this complex and critical topic. With coverage broad enough to appeal to general vehicle engineers and detailed enough to inform those with specialis.